Tumor-like corneal limbal lesions (Ukrainian Journal of Ophthalmology, 2025)
Background: Primary tumors of the cornea and sclera are extremely rare. Most tumors of this region are secondary neoplasms arising from adjacent ocular structures. Benign tumors, namely, conjunctival and/or corneal dermoid tumors and lipodermoids are most common.Purpose: To analyze three cases of tumor-like corneal limbal lesions and to assess treatment outcomes.Material and Methods: Three cases of tumor-like corneal limbal lesions were under our observation. All these were given a preliminarily diagnosis of a dermoid cyst or lipodermoid. Two patients underwent corneal lesion removal and subsequent keratoscleral plasty. In the third case, amniotic membrane was applied to the cornea after corneal lesion removal.Results: The intrasurgically removed tissue was sent for histological examination. The diagnosis of dermoid or lipodermoid was not confirmed in any case. In these three cases, histology showed thickened loose connective tissue composed of crossed bundles of collagen fibers and covered by stratified squamous epithelium with a non-uniform thickness profile, with evidence of mild acanthosis. Loose connective tissue comprised blood vessels and was mildly infiltrated with lymphocytes in one case.Conclusion: Limbal tumor-like lesions require thorough diagnostic evaluation including impression cytology is a must to differentiate benign from malignant epithelial lesions. In addition, the tissue removed during the surgical procedure must be sent to the pathological laboratory for histological verification of diagnosis.
Keywords: tumor-like lesions; corneal limbal area; dermoid cyst; lipodermoid; keratoscleral plasty; amniotic membrane